Pengelolaan Sistem Pengarsipan Dalam Mendukung Manajemen Mutu Pembelajaran Di Man 1 Parepare - Kasim, Indah Nur Afny; Ismail latief; Ni'mah Natsir; Muhammad Alwi; Fuad Guntara (IAIN Parepare, 2023)
The quality of learning is one of the important elements in the implementation of the learning process, the success or failure of a learning objective depends on the quality that is prepared and developed optimally. Archives are important for an institution as a provider of information needed in the management process to support the quality of learning. This research is a qualitative research by means of a case study. Data collection was carried out using the method of observation, interviews and documentation. This study aims to identify, find out problems and provide solutions related to managing the filing system in supporting learning quality management. To obtain data, the subjects of this study were the heads of Administration, staff and teachers at Madrasah Aliyah Negeri 1 Parepare. In addition, this study tested the validity of the data using the triangulation technique. The results of this study indicate that (1) Management of the filing system at MAN 1 Parepare has been carried out well but not yet structured. Because the party did not make a record book of borrowing and returning records so that it did not run efficiently. (2) Management of the filing system in supporting the quality of learning at MAN 1 Parepare has not been maximized in meeting the quality of learning because there are still deficiencies such as facilities and infrastructure and less efficient employee performance. (3) Obstacles in managing the filing system in supporting the quality of learning at MAN 1 Parepare, namely the lack of facilities both facilities and infrastructure, archival training is rarely conducted, there is no record retention schedule, the work of employees is quite busy.